2018
DOI: 10.3389/fimmu.2018.02529
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Polarization in Leishmaniasis: Broadening Horizons

Abstract: Leishmaniasis is a vector-borne neglected tropical disease that affects more than 700,000 people annually. Leishmania parasites cause the disease, and different species trigger a distinct immune response and clinical manifestations. Macrophages are the final host cells for the proliferation of Leishmania parasites, and these cells are the key to a controlled or exacerbated response that culminates in clinical manifestations. M1 and M2 are the two main macrophage phenotypes. M1 is a pro-inflammatory subtype wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(165 citation statements)
references
References 130 publications
7
147
0
1
Order By: Relevance
“…The infection resolution is attributed to the establishment of cell-mediated immunity, specifically the activation and differentiation of T lymphocytes that stimulate the production of cytokines, which induce the activation of infected mononuclear phagocytes and culminate with parasite elimination [54]. The differentiation of CD4+ T cells in T helper type (Th)1 upon antigen recognition on Major Histocompatibility Complex (MHC) II is predominantly associated with the development of a proinflammatory response, characterized by secretion of TNF-α, IL-1β, IL-6, IL-12, IL-18, and IL-23 cytokines; increased production of highly microbicidal ROS and reactive nitrogen species (RNS) (e.g., hydrogen peroxide, superoxide, hydroxyl radicals, and NO) via activation of the NADPH oxidase complex and inducible nitric oxide synthase (iNOS), respectively; and enhanced phagocytosis, leading to infection control especially in experimental models [54,55]. Meantime, an anti-inflammatory phenotype is correlated with a predominant Th2 response characterized by the production of IL-4, IL-13, IL-10, and Transforming Growth Factor (TGF)-β cytokines; enhanced arginase activity; polyamine biosynthesis; and IL-21-mediated down-regulation of iNOS, TNF-α, and Toll-like receptor (TLR)-4, favoring intracellular proliferation of Leishmania parasites and disease progression [56,57] (Figure 2).…”
Section: The Adaptive Immune Responses In Leishmaniasismentioning
confidence: 99%
See 1 more Smart Citation
“…The infection resolution is attributed to the establishment of cell-mediated immunity, specifically the activation and differentiation of T lymphocytes that stimulate the production of cytokines, which induce the activation of infected mononuclear phagocytes and culminate with parasite elimination [54]. The differentiation of CD4+ T cells in T helper type (Th)1 upon antigen recognition on Major Histocompatibility Complex (MHC) II is predominantly associated with the development of a proinflammatory response, characterized by secretion of TNF-α, IL-1β, IL-6, IL-12, IL-18, and IL-23 cytokines; increased production of highly microbicidal ROS and reactive nitrogen species (RNS) (e.g., hydrogen peroxide, superoxide, hydroxyl radicals, and NO) via activation of the NADPH oxidase complex and inducible nitric oxide synthase (iNOS), respectively; and enhanced phagocytosis, leading to infection control especially in experimental models [54,55]. Meantime, an anti-inflammatory phenotype is correlated with a predominant Th2 response characterized by the production of IL-4, IL-13, IL-10, and Transforming Growth Factor (TGF)-β cytokines; enhanced arginase activity; polyamine biosynthesis; and IL-21-mediated down-regulation of iNOS, TNF-α, and Toll-like receptor (TLR)-4, favoring intracellular proliferation of Leishmania parasites and disease progression [56,57] (Figure 2).…”
Section: The Adaptive Immune Responses In Leishmaniasismentioning
confidence: 99%
“…This manifestation can appear months or decades after the initial treatment, and it is possibly related to a suppressed immunity towards parasites that persist in the skin, producing skin rashes or non-ulcerating cutaneous lesions with high parasite loads [138]. It has been shown that monocytes and macrophages from these lesions exhibit increased expression of arginase-1, downregulation of TLR-2/4, and decreased production of ROS and RNS, associated with disease chronicity [55]. Interestingly, this type of response in the skin diverges from the predominant Th1 response induced systemically after VL treatment [13].…”
Section: Visceral Manifestationsmentioning
confidence: 99%
“…Previous studies have demonstrated that macrophages play a pivotal role in the outcome of Leishmania infection depending on type of macrophages; classically activated (M1) macrophages as efficient type against Leishmania parasites or alternatively activated (M2) macrophages as favoring survival and growth of Leishmania parasites (16,17). In response to different microbial stimuli and immune status of the microenvironment, naive macrophages (M0) differentiate to either M1 or M2 subpopulation with different patterns of cytokine production and distinct properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that macrophages play a pivotal role in the outcome of Leishmania infection depending on the type of macrophages: classically activated (M1) macrophages as e cient type against Leishmania parasites, or alternatively, activated (M2) macrophages as favoring survival and growth of Leishmania parasites [16,17]. In response to different microbial stimuli and immune status of the microenvironment, naive macrophages (M0) differentiate into either M1 or M2 subpopulations with different patterns of cytokine production and distinct properties.…”
Section: Introductionmentioning
confidence: 99%